Efektivitas Pendekatan Pembelajaran Realistic Mathematics Education (RME) Berbasis Etnomatematika untuk Mendukung Literasi Matematis Siswa SMP - Rizal Afandi; Irwani Zawawi; Fatimatul Khikmiyah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Mathematics learning can be done by applying it in everyday life, one of which is through available local culture or through available cultural practices. This study aims to determine the effectiveness of learning the Realistic Mathematics Education approach based on ethnomathematics to support the mathematical literacy of junior high school students. The effectiveness indicators used in this study are: students' response to learning, students' learning outcomes, students' activities, and teachers' ability to manage learning. The type of research used is descriptive research. The research subjects used were VIII grade students of YPI Darussalam 2 Cerme Junior High School, Gresik Regency, East Java consisting of 30 students. The data collection technique used in this study used an observation sheet of the teacher's ability to manage learning and student activities. The next instrument uses a questionnaire sheet of students' responses, and to determine student learning outcomes using student learning outcomes tests. Based on the results of the study showed that: 1) The teacher's ability to manage learning is 86.67% of the maximum score with a very good category, 2) Student activities show a percentage of 84.67%, including in the good category, 3) The response given by students in the good category with a percentage of 74.8%, and 4) The completeness of students' learning outcomes in the good category with a percentage of 76.67% of the maximum score. The conclusion that can be drawn from this research shows that ethnomathematics-based RME learning is effective in supporting the mathematical literacy of junior high school students.